(−)‐Isoscopariusin A, a Naturally Occurring Immunosuppressive Meroditerpenoid: Structure Elucidation and Scalable Chemical Synthesis. Issue 23 (30th March 2021) - Yan, Bing‐Chao; Zhou, Min; Li, Jian; Li, Xiao‐Nian; He, Shi‐Jun; Zuo, Jian‐Ping; Sun, Han‐Dong; Li, Ang; Puno, Pema‐Tenzin
Abstract: (−)‐Isoscopariusin A was isolated from the aerial parts of Isodon scoparius . Chemical synthesis and spectroscopic analysis established its structure as an unsymmetrical meroditerpenoid bearing a sterically congested 6/6/4 tricyclic carbon skeleton with seven continuous stereocenters. A gram‐scale synthesis was achieved in 12 steps from commercially available (+)‐sclareolide. A cobalt catalyzed, hydrogen atom transfer‐based olefin isomerization was used to prepare a trisubstituted alkene, which underwent stereoselective [2+2] cycloaddition with a substituted keteniminium ion generated in situ from the corresponding amide. The cyclobutanone product was further elaborated into the fully substituted cyclobutane core through face‐selective homologation, and the two side chains were installed by using nickel‐catalyzed cross‐electrophile coupling and carbodiimide‐mediated esterification, respectively. (−)‐Isoscopariusin A displayed selective inhibition of T‐cell proliferation. Abstract : Reported herein is the isolation, structure determination of (−)‐isoscopariusin A by spectroscopic analysis and concise chemical synthesis. The unprecedented meroditerpenoid bears a 6/6/4 tricyclic carbon skeleton with seven continuous stereocenters, and exhibits selective inhibition of T‐cell proliferation. A gram‐scale synthesis was achieved in 12 steps from (+)‐sclareolide.